LONELINESS EXPERIENCED BY INFORMAL CAREGIVERS OF THE CHRONICALLY ILL IN THEIR HOMES. PROPOSED SOLUTIONS AND PRACTICAL RECOMMENDATIONS FOR LOCAL COMMUNITIES - Krakowiak, Piotr; Wasilewska-Ostrowska, Katarzyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Loneliness experienced by family caregivers of the chronically ill in their homes is described starting with different aspects of solitude in social sciences. Family care as part of informal care should cooperate with formal careers from health and social systems. Welfare institutions and home care in Poland are described in front of growing challenges of ageing societies in Europe. Good practices and practical recommendations for local communities, including better coordination of care, as well as support for family caregivers at risk of loneliness and other difficulties are offered as a conclusion of this report.